Fuzzy based sensorless tracking controller on the dual-axis PV panel for optimizing the power production - Bandiyah Sri Aprilia; Muhammad Zakiyullah Romdlony; Jangkung Raharjo; Yogi Ghifari Sidik (JURNAL INFOTEL, 2021)
In general active sun trackers move because they respond to light sensors that measure the intensity of sunlight. However, sensor-based trackers are usually more expensive than sensor-less trackers. In addition, based on several studies, a comparison between the sensor and sensorless based tracker only reports lower tracking error and higher power generation for sensor-based than sensorless tracker. However, it does not include an analysis of energy use on the sensor. Therefore, this study aims to design a sensorless closed-loop tracking system for solar panels with two degrees of freedom. The tracking controller in this study is based on the Fuzzy Logic Controller (FLC) method. In this study, a dual-axis PV can increase power output by 20.2% compared to a fixed PV (0 ° axis position). In comparison to a fixed PV, dual-axis PV adjusts the solar panel perpendicular to the sun's position to optimize electrical conversion.